Three-dimensional hydraulic modeling of particle deposition on the patterned isopore membrane in crossflow microfiltration - Choi, Dong-Chan (2017)
Patterned membranes have been proposed as a promising solution to membrane fouling in membrane processes for water treatment. CFD modeling studies were carried out to elucidate the anti-fouling effect of patterned membranes However, patterned membranes prepared usually by a phase inversion method are more likely to have broad pore size distributions and most modeling studies are based on two-dimensional space despite the three-dimensional pattern geometry. In this study, a patterned isopore membrane with reverse-pyramid patterns on its surface and a narrow pore size distribution was prepared from UV-curable polymer by the soft lithographic method. Factors affecting particle depositions on patterned isopore membranes were investigated during the crossflow microfiltration of different micro-sized particles and their mixture. The extent of particle deposition was largely dependent on crossflow velocity, pore water flux, and particle size. Particularly, the ratio of crossflow velocity to pore water flux mostly governed the extent of particle depositions (i.e., membrane fouling) on the patterned membrane surface and 3-D modeling based on computational fluid dynamics was also conducted to predict the formation of two distinct stream lines (bulk and vortex) and elucidate the mechanisms of anti-fouling characteristics of patterned membranes.